Recent progress in calcium carbonate nanoparticles for cancer therapy: design strategies and clinical prospects - Xi Deng; Mohammad Yusuf Zanna; Hamidu Ahmed; Norsharina Ismail; Kim Wei Chan; Norhaizan Mohd Esa; Ahmad Faizal Abdull Razis; Md Zuki Abu Bakar; Zhongming Yang (Materials Research Express)
Calcium carbonate nanoparticles (CaCO _3 NPs) have garnered broad attention as promising nanocarriers for cancer therapy owing to their biocompatibility, pH sensitivity, ease of synthesis, and tunable surface properties. These NPs remain stable under physiological conditions but rapidly dissolve in the acidic tumor microenvironment, enabling controlled drug release. Various synthesis methods, including solution precipitation, microemulsion, gas diffusion, flame synthesis, biomineralization, and mechanical ball milling techniques, have been explored to optimize their physicochemical properties. CaCO _3 NPs can be functionalized with targeting ligands, polymers, and biomolecules to enhance therapeutic efficacy and selectivity. Their ability to co-deliver multiple drugs and achieve synergistic therapeutic effects further enhances their potential in cancer treatment. This review uniquely integrates synthesis strategies, drug delivery mechanisms, and clinical challenges, offering systematic insights to bridge laboratory advances with clinical translation. Moreover, critical challenges such as stability, reproducibility, and potential safety concerns are discussed, alongside strategies to overcome these limitations. Despite their promise, further research is needed to refine synthesis techniques, assess long-term safety, and improve clinical translation. By addressing these challenges, CaCO _3 NPs could become a valuable tool for targeted cancer therapy, offering enhanced treatment efficacy with reduced side effects.